O "Zbiorze zadań i pytań z literatury polskiej dla uczniów szkoły średniej" Stanisława Adamczewskiego = On "A collection of exercises and questions regarding polish literature - for grammar schools" by Stanisław Adamczewski - Świętosławska, Teresa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper discusses a forgotten publishing canon for handbooks, employed in the 1920's, serving a heuristic model of getting acquainted with literature. S. Adamczewski's "A Collection of Exercises and Questions Regarding Po'lish Literature for Gra?mmar Schools" was one of such handbooks. The author proved the didactic values of heuristics as a method of research.
Keywords: Adamczewski, Stanisław (1883-1952)